Folliculitis due to olive oil. - Tagliavanti, M. (European Journal of Pediatric Dermatology, 2015)
There are two known clinical pictures of folliculitis due to fat substances, namely acne involving the forehead in blacks using to slick their hair and folliculitis of the workers with mineral oils (1, 2). In both cases it is assumed that the oils can act either by occluding the follicular ostia or irritating the opening of the hair follicle (1, 2). In acne of black men the frontal region is mainly affected, while folliculitis due to mineral oils mainly affects the upper limbs and buttocks. We did not find in the literature other cases of folliculitis arising after massage with olive oil; however, the pathogenetic role of olive oil in our case is supported both by the time of occurrence of the lesions – a few days after the suspension of the massage – and the site of the lesions, which are those where massages are practiced, i.e. the clavicular and scapular regions and the upper back with non involvement of the interscapular area.